2018
DOI: 10.1021/acsaem.7b00111
|View full text |Cite
|
Sign up to set email alerts
|

Review on Ammonia Absorption Materials: Metal Hydrides, Halides, and Borohydrides

Abstract: Ammonia is well-known as a hydrogen carrier owing to its high hydrogen capacity (17.8 wt %). However, the toxicity and the high storage pressure limit the application of ammonia. Consequently, storing ammonia in solid state has become the promising method to utilize ammonia for practical applications. In this review, ammonia absorption properties of metal hydrides, halides, and borohydrides to form metal amides and metal ammine complexes with various coordination numbers have been systematically summarized. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 81 publications
1
62
0
Order By: Relevance
“…Rb, Cs, Fr, Sr, Ba, and Ra borohydrides are not included owing to either low capacity (<6 wt.%) or Td higher than 600 • C. In the case of Be borohydride, with~21 wt.% H 2 , it is not included because Be is extremely toxic. As seen, LiBH 4 contains the highest gravimetric capacity but has a relatively high decomposition temperature [1][2][3][4][5][6][7]. However, most of the hydrogen release from LiBH 4 occurs above 500 • C and at a slow rate.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Rb, Cs, Fr, Sr, Ba, and Ra borohydrides are not included owing to either low capacity (<6 wt.%) or Td higher than 600 • C. In the case of Be borohydride, with~21 wt.% H 2 , it is not included because Be is extremely toxic. As seen, LiBH 4 contains the highest gravimetric capacity but has a relatively high decomposition temperature [1][2][3][4][5][6][7]. However, most of the hydrogen release from LiBH 4 occurs above 500 • C and at a slow rate.…”
Section: Introductionmentioning
confidence: 91%
“…In the same year, Jin et al were pioneers in successful destabilizing LiBH 4 with CeH 2 [83]. They assessed the theoretical enthalpy change of both LiBH 4 -Ce and LiBH 4 -CeH 2 systems (27.6 and 44.1 kJ mol −1 , respectively) and predicted a significant lower dissociation temperature than the individual hydrides (171 • C versus >350 • C [1]), according to Reaction (7). Experimental studies confirmed that the 6LiBH 4 -CeH 2 composite catalyzed by 0.2TiCl 3 release hydrogen at a temperature lower than LiBH 4 melting forming CeB 6 and LiH as solid products, in agreement with thermodynamic calculations.…”
Section: Destabilization Of Libh 4 By Rare Earth (Re) Metal Hydridesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, near-total requirement on fossil fuels has brought about two serious trepidations: increased rate of global warming and insecurity of oil imports. [1][2][3] To rectify the two issues, hydrogen is used as an alternate next-generation energy source because its burned by-product is only pure water vapors compared with the carbonaceous fossil fuels. 4 One of the most challenges is the safety and transportation of hydrogen in a compact and affordable storage system.…”
Section: Discussionmentioning
confidence: 99%
“…These energy sources are invaluable impact of our community toward industrialization. Recently, near‐total requirement on fossil fuels has brought about two serious trepidations: increased rate of global warming and insecurity of oil imports . To rectify the two issues, hydrogen is used as an alternate next‐generation energy source because its burned by‐product is only pure water vapors compared with the carbonaceous fossil fuels .…”
Section: Introductionmentioning
confidence: 99%